2015
DOI: 10.1186/s40816-015-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Herbal treatment in asthma and COPD – current evidence

Abstract: Asthma and COPD are chronic inflammatory respiratory diseases affecting millions of people worldwide and increasing in prevalence. Current treatment options for both conditions aim to alleviate symptoms, improve patient quality of life and prevent disease progression rather than cure the underlying condition itself. Treatments available to patients include anti-inflammatory therapies, bronchodilators and inhaled corticosteroids. While these treatments have been deemed effective at alleviating disease symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…Up to 79% of adult patients with asthma used different complementary and alternative treatments including herbal medicines, but the evidence for such treatments' effectiveness in asthma is very limited (Slader et al ., ). A review of plant‐based medicines used in asthma management found that the evidence is still unconvincing and there is a need for a proper scientific research to support the use of plant‐based medicines in asthma (Clarke et al ., ). Therefore, phytotherapy remains a commonly used but poorly investigated element of asthma treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Up to 79% of adult patients with asthma used different complementary and alternative treatments including herbal medicines, but the evidence for such treatments' effectiveness in asthma is very limited (Slader et al ., ). A review of plant‐based medicines used in asthma management found that the evidence is still unconvincing and there is a need for a proper scientific research to support the use of plant‐based medicines in asthma (Clarke et al ., ). Therefore, phytotherapy remains a commonly used but poorly investigated element of asthma treatment.…”
Section: Introductionmentioning
confidence: 97%
“…It is possible that the bronchodilatory effects of compounds such as N. sativa could be enhanced if formulated as inhaled therapy with delivery of the active compounds directly to the airway. [8] Tianjiu therapy in Sanfu days Zhu et al studied the effect of Tianjiu therapy in Snafu days for treatment of asthmatic children. Tianjiu therapy in Sanfu days is a classic prevention treatment for asthma [37] Sanfu Days means the three hottest days in a year, which are calculated by ancient calendar.…”
Section: Nigella Sativamentioning
confidence: 99%
“…[36] Atropine remains a treatment of cardiac bradyarrhythmias, and has been used successfully in the treatment of conditions such as amblyopia, also known as lazy eye. [8] Various phytomedicines for treating asthma are available. These are Oregano, GinkoBiloba, Ginger, Garlic, Slippery Elm, Liquorice, Turmeric, Lemongrass, Stinging Nettle, and Bishop's Weed.…”
Section: Phytomedicine In the Treatment Of Asthma And Copdmentioning
confidence: 99%
See 2 more Smart Citations